Will Wage Setters Ever Stagger Decisions? - Fethke, Gary; Policano, Andrew (Quarterly Journal of Economics, 1986)
Gary Fethke, Andrew Policano; Will Wage Setters Ever Stagger Decisions?*, The Quarterly Journal of Economics, Volume 101, Issue 4, 1 November 1986, Pages 867–87